2016
DOI: 10.1111/ceo.12692
|View full text |Cite
|
Sign up to set email alerts
|

Expression of visfatin in the diabetic rat retina

Abstract: Background: Visfatin has been found in adipose tissue, liver and kidney of healthy and diabetic people, with its expression being increased in the aforementioned tissues in diabetes. Based on the former researches, visfatin may exist in the retina and affect the development of diabetic retinopathy. The expression of visfatin in Sprague-Dawley rats' retina, which may carve a path to study the pathogenesis of diabetic retinopathy, was investigated by this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Although the exact nature of the newly discovered Pros, Grn and visfatin signaling pathways in cornea remains unclear, it has been observed that these three signaling pathways were associated with retina, including that Pros1 mutation correlates with inherited retinal degenerations, 58 Grn deficiency results in photoreceptor degeneration in mouse retina 59 and visfatin expression in diabetic rat retina. 60 Although chemerin has been shown to promote vessel growth in the mouse corneal angiogenesis model, 61 its specific role in the cornea remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact nature of the newly discovered Pros, Grn and visfatin signaling pathways in cornea remains unclear, it has been observed that these three signaling pathways were associated with retina, including that Pros1 mutation correlates with inherited retinal degenerations, 58 Grn deficiency results in photoreceptor degeneration in mouse retina 59 and visfatin expression in diabetic rat retina. 60 Although chemerin has been shown to promote vessel growth in the mouse corneal angiogenesis model, 61 its specific role in the cornea remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, visfatin binds to the insulin receptor-1 and exerts an insulin-like effect ( 230 ). Being adipocytokines with various pleiotropic effects visfatin exerts IR, inhibits WAT oxidative stress and inflammation, promotes vascular reparation, and suppresses ischemia-induced apoptosis of cardiac myocytes mainly through up-regulation of proinflammatory cytokines, such as TNF-α and MCP-1 ( 231 ). On the other hand, visfatin also up-regulates NF-κB in endothelial progenitor cells inducing apoptosis of these precursors leading to a decrease in the number of circulating endothelial progenitor cells with angiopoietic activity ( 232 , 233 ).…”
Section: Adipose Tissue Dysfunction and Heart Failurementioning
confidence: 99%